The Usage of Dummy Variable for VAT Forecasting of the Tax Administration in the Slovak Republic - Pavlik, Martin (Wykorzystanie zmiennych sztucznych w prognozowaniu podatku VAT w analizie wpływów podatkowych na Słowacji, 2008)
The State Treasury was established by State Treasury Act in 2002. The Act ordered the Tax Directorate of the Slovak Republic to send the tax forecasts to the State Treasury. The act does not specify the form how forecasts should be sent. We send forecasts on a monthly basis for the next three months. The closest month is forecast per day. The aim of the article is to show how we make monthly forecasts. The fact that tax forecasts are made on a monthly basis influenced the explanatory variables. Classical macroeconomic variables cannot be used, because they are not observed on a monthly basis. Moreover, another very important fact that influenced the forecasts is the Tax Reform from 2004 and the acceptance of the Slovak Republic for a member of the European Union. (fragment of text)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 6, s. 41-53